DATA VISUALISASI TINGKAT KENAIKAN LIMBAH SAMPAH DI INDONESIA - Madyatmadja, Evaristus Didik; Widjaja, Samuel Axel; Haryo Pangukir, Joseph Priadi; Budiharjo, Matthew; Rianky, Rianky; Heryanda, Oktavian (Infotech: Journal of Technology Information, 2023)
Waste or garbage is a leftover material that has no use or is disposed of after daily activities by humans. The purpose of this research is to know whether waste in Indonesia has increased or not in the last three years and to find out what type of waste is the most in the last three years, and finally, what province has the largest pile of waste in the last three years. This research uses the method that has some procedures. They are acquired, parse, filter, mine, represent, refine, and interact. The visualization data used is using Microsoft Excel. There are two pieces of data, data on waste generation per year and data on the most types of waste from 2020 to 2022 in Indonesia based on SIPSN data. Data from SIPSN already in Microsoft Excel is inserted into Power BI by selecting "Get data ''; The data is processed into a table and started to be able to filter the data that has appeared. Data is then filtered to remove unwanted data. Waste accumulation in Indonesia has tended to decrease in the last three years. Various provinces in Indonesia have different figures depending on the population and advancement of infrastructure in the province. Last three years, food waste has become the highest number of waste. People aren't aware that the food scraps they consume can affect the total amount of waste/garbage. DKI Jakarta Province is the province that has the most waste pile. It is because DKI Jakarta province is a province that has a large population.